DETERMINATION OF THE RISK FACTORS ASSOCIATED WITH PROBLEMATIC SOCIAL MEDIA USE AMONG ADOLESCENTS OF ALBANIAN AND MACEDONIAN DESCENT IN NORTH MACEDONIA - OSMANI BALLAZHI, Sheruze; NEZIRI, Ibrahim; BEXHETI, Luljeta; SOTIROSKA, Kalina (University of Tetova, 2024)
Problematic social media use turns out to have effects on many dimensions of teenagers' lives, including emotional well-being, social interactions, and interpersonal relationships. The focus of research is oriented directed towards identification, in addition to its effects, the predictive factors associated with problematic use of social media. The purpose of this study is to predict the effect of family support, school support and school well-being on the problematic social media use among adolescents in North Macedonia. The study included 5144 adolescents 11, 13 and 15 years old, of which 48.4% are boys and 51.6% are girls. Considering the structure of the population in the country, 66.6% are young Macedonians and 33.4% Albanians. The data presented are part of the cross-sectional study "Health and Behaviour of School-aged Children", collected during 2022. The results of the research showed that family support is a predictor of problematic social media use for Macedonian and Albanian girls and boys, whereas teacher support did not emerge as a determinant of problematic social media use. Prediction role of classmates’ support and school pressure are also discussed.